2016
DOI: 10.1016/j.jtrangeo.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Changing times – A decade of empirical insight into the experience of rail passengers in Great Britain

Abstract: In the last decade the number of rail passenger journeys in Great Britain has increased by half and car trips per person are down by a tenth. Meanwhile there has been significant growth in internet use and ownership of smartphones. Travel patterns are changing in tandem with adoption of digital age innovations. At a time when Britain is also poised to invest tens of billions of pounds in high speed rail, this paper examines how the experience of rail Historically, transport analysis has stemmed from the premis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 16 publications
3
35
0
Order By: Relevance
“…First, our findings bring nuance to the dominant idea that mobile devices like laptops, headphones and mobile phones contribute to incivility (Valentine 2008), detachment (Hatuka and Toch 2016) and ignorance (Kumar and Makarova 2008;Kim 2012). Certainly, these devices have greatly reconfigured (the perception of) travel time (Jain and Lyons 2008;Lyons, Jain, and Weir 2016) and social relations in public spaces. Our observations illustrate that passengers are often very self-absorbed; gazing at their screens, seemingly shutting others out.…”
mentioning
confidence: 76%
See 4 more Smart Citations
“…First, our findings bring nuance to the dominant idea that mobile devices like laptops, headphones and mobile phones contribute to incivility (Valentine 2008), detachment (Hatuka and Toch 2016) and ignorance (Kumar and Makarova 2008;Kim 2012). Certainly, these devices have greatly reconfigured (the perception of) travel time (Jain and Lyons 2008;Lyons, Jain, and Weir 2016) and social relations in public spaces. Our observations illustrate that passengers are often very self-absorbed; gazing at their screens, seemingly shutting others out.…”
mentioning
confidence: 76%
“…First, they are frequent train riders out of necessity, as opposed to, for example, the age group between 30 and 50 who often have the option to travel by car (Kampert et al 2017). They are the potential passengers of the future that need to be attracted or retained, yet research has shown younger people have more negative experiences of public transport than older people (Clayton, Jain, and Parkhurst 2016) and consequently find their travel time less worthwhile (Watts and Urry 2008;Lyons et al 2013;Lyons, Jain, and Weir 2016). Moreover, they are often seen as 'perpetrators of disruptive acts' (Ocejo and Tonnelat 2014, 497) and the digital generation that was 'born with a mouse in their hands and a computer screen as their window to the world' (Lindstrom and Seybold 2003, 24).…”
Section: Observationsmentioning
confidence: 99%
See 3 more Smart Citations